2022
DOI: 10.1007/s00170-022-08731-1
|View full text |Cite
|
Sign up to set email alerts
|

Micro-texturing of polymer surfaces using lasers: a review

Abstract: Micro- and nanoscale structures produced on surfaces of metals, polymers, ceramics, and glasses have many important applications in different fields such as engineering, medical, biological, etc. Laser ablation using ultrashort pulses has become the prominent technique for generating different surface structures for various functional applications. Ultrashort laser ablation proved to be ideal for producing structures with dimensions down to the nanometre scale. In comparison to other texturing techniques emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 123 publications
2
21
0
Order By: Relevance
“…In value, the fluence is different, depending on the material. For example, for polymers it is between 0.1 to 1 J/cm 2 , while for inorganic insulators it is between 0.5 and 2.0 J/cm 2 [2]. Related to the present study, Moldovan E. et al [24] showed a decrease in fluence values from 8.49 J/cm 2 to 2.55 J/cm 2 , in the frequency range of 30-100 kHz.…”
Section: Introductionsupporting
confidence: 71%
See 3 more Smart Citations
“…In value, the fluence is different, depending on the material. For example, for polymers it is between 0.1 to 1 J/cm 2 , while for inorganic insulators it is between 0.5 and 2.0 J/cm 2 [2]. Related to the present study, Moldovan E. et al [24] showed a decrease in fluence values from 8.49 J/cm 2 to 2.55 J/cm 2 , in the frequency range of 30-100 kHz.…”
Section: Introductionsupporting
confidence: 71%
“…Laser surface texturing (LST) is a widely used method worldwide for surface functionalization [1][2][3][4], being used in various fields: medical implants [5][6][7][8][9][10][11], wettability tuning [12], optical properties [13,14], hybrid joining [15][16][17], increasing adhesion [18], or cutting tools [19][20][21][22]. The materials that are the object of microtexturing are varied, from dentin and enamel materials, to polymers, ceramics, ferrous and non-ferrous metallic materials, and finally composite materials, in various domains such as engineering, medicine, bioengineering, etc.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Not less important in the selection of PC was the fact that this polymer undergoes minimal physico-chemical changes when is subjected to LA and NIL procedures, compared with other patterning technologies such as laser texturing with longer pulses (i.e. nanosecond (ns) and microsecond (μs) pulses), electrochemical machining, micromilling and mechanical texturing [51].…”
Section: Discussionmentioning
confidence: 99%